The interpretation of the certain provisions of the Air Code of Ukraine in the criminal-legal aspect - Багіров, Сергій Рамізович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article highlights the issue of relationship of air law and criminal law in Ukraine. Attention is focusedon the controversial moments, when the legislative requirements of the Air Code of Ukraine do not complywith principles of the theory of criminal law. The author criticizes certain provisions of the Air Code ofUkraine from the standpoint of the doctrine of criminal law.